The story of arthur truluv ebook A novel. - Berg, Elizabeth (Mason, 2017)
“I dare you to read this novel and not fall in love with Arthur Truluv. His story will make you laugh and cry, and will show you a love that never ends, and what it means to be truly human.”—Fannie Flagg An emotionally powerful novel about three people who each lose the one they love most, only to find second chances where they least expect them “Fans of Meg Wolitzer, Emma Straub, or [Elizabeth] Berg’s previous novels will appreciate the richly complex characters and clear prose. Redemptive without being maudlin, this story of two misfits lucky to have found one another will tug at readers’ heartstrings.”— Booklist For the past six months, Arthur Moses’s days have looked the same: He tends to his rose garden and to Gordon, his cat, then rides the bus to the cemetery to visit his beloved late wife for lunch. The last thing Arthur would imagine is for one unlikely encounter to utterly transform his life.  Eighteen-year-old Maddy Harris is an introspective girl who visits the cemetery to escape the other kids at school. One afternoon she joins Arthur—a gesture that begins a surprising friendship between two lonely souls. Moved by Arthur’s kindness and devotion, Maddy gives him the nickname “Truluv.” As Arthur’s neighbor Lucille moves into their orbit, the unlikely trio band together and, through heartache and hardships, help one another rediscover their own potential to start anew. Wonderfully written and full of profound observations about life, The Story of Arthur Truluv is a beautiful and moving novel of compassion in the face of loss, of the small acts that turn friends into family, and of the possibilities to achieve happiness at any age. Praise for The Story of Arthur Truluv “For several days after [finishing The Story of Arthur Truluv ], I felt lifted by it, and I found myself telling friends, also feeling overwhelmed by 2017, about the book. Read this, I said, it will offer some balance to all that has happened, and it is a welcome reminder we’re all neighbors here.” — Chicago Tribune “Not since Paul Zindel’s classic The Pigman have we seen such a unique bond between people who might not look twice at each other in real life. This small, mighty novel offers proof that they should.” — People, Book of the Week